Macronutrients screening on the growth and development of Stevia rebaudiana (Bertoni) in vitro shoot culture and the yielding of stevioside and rebaudioside A. / Fakhrul Razin Hasan - Hasan, Fakhrul Razin (2015)
Stevia rebaudiana (Bertoni) is a herbaceous plant which has an increasing demand in agricultural industry worldwide. This is due to the presence of the sweet glycosides in the leaves that are hundreds times sweeter than sugar and have zero calories.Previously, studies were focused on the increasing its yield such as growth regulator manipulation, light, water and temperature controlling in greenhouse and genetic modification of the herb. However, no study had been done on the macronutrients manipulation in Stevia rebaudiana (Bertoni). Therefore, the novelty of this study is, it is the first study in discovering the effects of macronutrients manipulation in Stevia rebaudiana (Bertoni) in vitro plantlets. This study aimed at screening the growth and development of Stevia rebaudiana (Bertoni), and the stevioside and rebaudioside A yield in different concentration strength of macronutrients. It was done by using onefactor-at-a-time (OFAT) technique. Different parts of the in vivo plants were separated and extracted in different solvents and analysed by using HPLC. Meanwhile, the sterile shoot tip explants were cultured onto MS basal media. After 1 month, several of these sterile plantlets were extracted in different solvents and analysed by using HPLC. The remained sterile plantlets were continued regenerated and multiplied to increase their quantities. Media with manipulated macronutrients (N, K, Ca, Mg, P and S) were prepared in different concentrations strength (0, 0.5x, lx, 2x, 4x and 8x) for each macronutrient element. The sterile plantlets were then cultured onto these modified media. After 1 month, the whole plantlets were oven dried and ground into powder for extraction in different solvents and analysed by using HPLC. Findings showed that in vitro shoots contain significantly high concentration of stevioside (22.63±0.25mg/ml), while in vivo leaves contain significantly high concentration of rebaudioside A (2230.40±26.72 mg/ml) as compared to other parts of Stevia rebaudiana (Bertoni). Results from this study also showed that the aqueous solvent was the best solvent to extract stevioside while methanol was the best solvent to extract rebaudioside A.Moreover, 4x K concentration produced highest number of leaves (22.00±2.21), highest number of nodes (9.40±0.85), highest fresh biomass (0.07±0.01g) and highest dry biomass (0.006±0.001g), while 8x S produced the highest shoot length (3.83±0.39cm). There is no direct relationship between macronutrients concentration increment towards physical characteristics and biomasses of Stevia rebaudiana (Bertoni) shoot culture. The proposed macronutrient concentrations in optimizing the growth and development of Stevia rebaudiana (Bertoni) shoot culture are lx N, 4x K, 8x Ca, 4x Mg, 8x P and lx S. Furthermore,media without Mg (Ox concentration strength) yielded the highest stevioside concentration (4.57±0.02mg/ml), while media without Ca (Ox concentration strength) yielded the highest rebaudioside A concentration (1709.10±6.44mg/ml). There is no direct relationship between the macronutrients concentration increment towards the stevioside and rebaudioside A yield. The proposed macronutrients concentration strength in yielding the highest stevioside concentration are 8x N, 0 K, 0.5x Ca, 0 Mg,8x P and 2x S while the proposed macronutrient concentration strength in yielding the highest rebaudioside A concentration are 4x N, 2x K, 0 Ca, 2x Mg, 0 P and 0.5x S. Findings from this study also showed that there is no direct relationship between the physical characteristics and biomass towards the stevioside and rebaudioside A yield.